(untitled) (Journal of the College of Education for Women, 2018)
A survey to show the reality of educational guidance in schools in Baghdad Rusafa 3 from the point of view of educational guides. It used the analytical descriptive technique. The research community consists of () male and female advisors in schools of Baghdad. The sample was haphazard( 51\.) The questionnaire was made and it consists (50) items. The research statistics have been analyzed by (SPSS), The questionnaires have been used in the first term in (2017-2018) and the results showed the relationship between the advisor and other teachers, the advisor and students fathers and the local society. According to the results, the research made some recommendations and suggestions.